Please explain the process not just the answer. Thank you!

Let's assume that length of the second leg is * x* ft, then length of the hypotenuse is

*ft.*

**(x + 1)**Now, let's apply the Pythagorean theorem: (x + 1)

^{2}= x

^{2}+ 7

^{2}

x

^{2}+ 2x + 1 = x

^{2}+ 49

2x = 48 ---> x =

*(second leg)*

**24 ft**x + 1 =

*(hypotenuse)*

**25 ft**
## Comments

Hi Jay! An interesting pattern emerges: square the given side, subtract by one, and cut in half ... given 5, 25-1 is 24, cut in half to 12 ===> 5,12,13 triangle. This "all-integer" triangle "recipe" works only for an odd given side. How 'bout given 9? 81-1 is 80, cut in half to 40 ==> 9,40,41; next is 11,60,61 Best regards :)

Hi Brad, that idea is good one!!